"Verwandlung" Dore Pejačević sluhom Arnolda Schönberga - Kos, Koraljka (Muzikološki zbornik, 2007)
Croatian composer Dora Pejačević (1885-1923) wrote 1915 an occasional composition Verwandlung for alto, violin and organ or piano on verses by Karl Kraus for the wedding of her friend Sidonija Nádherný von Borutin which eventually didn't take place. Kraus planed to have performed the piece on one of his literary readings on 4th of December 1916 in Vienna and he showed the work Arnold Schonberg who praised it and especially commented one place in the score. Three strophes of Kraus's poem are the foundation for an extensive lyrical scene with instrumental interlude between the second and the third strophe which has a special place in the whole work. Late romantic harmony with labile tonality carries the emphasis of the expression. Kraus's verses evidently pushed the composer towards free musical flow and original harmony.
Keywords: glasba; harmonija; Kraus, Karl, 1874-1936; music; Pejačević, Dora, 1885-1923; Schönberg, Arnold, 1874-1951